Human factors integration in complex systems: awareness, challenges and strategies - Saif Rashed Almazrouei, Sara; Camelia, Fanny; Leal, Raul; Ferris, Timothy L. J.; Kaya, Gulsum Kubra; Chatzimichailidou, Mikela (Taylor & Francis, 2025)
Human Factors Integration (HFI) is crucial for the development of complex systems, ensuring both effectiveness and safety. This research presents a case study on HFI awareness and implementation in a missile and guided weapons development company, focusing on the application of HFI principles, the challenges faced, and potential areas for improvement. Semi-structured interviews were conducted with twelve respondents across various roles in the company, and thematic analysis was used to analyse interview data. Key themes were identified concerning HFI awareness, organisational dynamics and practical challenges. The findings revealed significant gaps in formal HFI training, limited integration of HFI into project specifications and inconsistent end-user involvement. Organisational and cultural resistance hindered HFI due to cost and timeline constraints. The study suggests that early integration of HFI into the Systems Engineering process, alongside enhanced training programmes and a cultural shift towards prioritising HF, are essential for overcoming these challenges.
Keywords: Human Factors (HF); Human Factors Integration (HFI); systems engineering; defence industry; complex systems; 5201 Applied and Developmental Psychology; 4201 Allied Health and Rehabilitation Science; 42 Health Sciences; 4207 Sports Science and Exercise; 52 Psychology; Human Factors